Knowledge, attitudes, and practices of health care waste management among Zambian health care workers - Colleen M. Leonard; Chipwaila Choolwe Chunga; Justine M. Nkaama; Kutha Banda; Chilekwa Mibenge; Victor Chalwe; Godfrey Biemba; Sandra Chilengi-Sakala; Florence Kabinga Mwale (Public Library of Science (PLoS), 2022)
Poor management of health care waste poses a serious threat to the health of health care workers, patients and communities. In developing countries, adequate health care waste management (HCWM) is often a challenge. To address this, the Zambian Health Services Improvement Project with HCWM as a component, was implemented in five Zambian provinces (Luapula, Muchinga, Northern, North-Western and Western Provinces), under which this cross-sectional study was conducted to identify the knowledge, attitudes, and practices of health care workers on HCWM. Fifty government hospitals and health posts from five provinces in Zambia were included in the study. Data was collected using a mixed-methods approach, which included surveys with health care workers (n = 394), in-depth interviews (n = 47) with health officials at the provincial, district, and facility levels, and observational checklists (n = 86). Overall, knowledge of proper waste segregation was average (mean knowledge score 4.7/ 7). HCWM knowledge varied significantly by job position (p = 0.02) and not by facility level, years of service, nor prior training. Only 37.3% of respondents recalled having received any sort of HCWM training. Poor waste segregation practice was found as only 56.9% of the facilities used an infectious waste bag (yellow, red or orange bin liner) and a black bag for general waste. This study revealed that only 43% of facilities had a functional incinerator on site for infectious waste treatment. Needle sticks were alarmingly high with 31.3% of all respondents reporting a prior needle stick. The system of HCWM remains below national and international standards in health facilities in Zambia. It is imperative that all health care workers undergo comprehensive HCWM training and sufficient health care waste commodities are supplied to all health facility levels in Zambia.